The service delivery standards of the BRAC Community Empowerment Programme (CEP) - Munrat, P. Sabeth Hasnain Ahmed (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.